Rewriting of the Colonial Narrative of the Tiger in R.K. Narayan's a Tiger for Malgudi - Charitha M.R.; G.M. Tungesh, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Animals have always been used by humans to fulfill their needs; in agriculture, as food and for companionship from times immemorial. Fables portraying animals who speak are a part of Indian folklore. The question of animals has been a constant preoccupation in recent times because of the marginalized state of some animals. Eco criticism, Post Humanism and Literary Animal Studies are three emerging interdisciplinary fields of research in World Literature that try to address the issue of rapid destruction of the environment, reconstruction of the animals and the exploitation of animals. In an Eco system where every organism is connected, destruction of one species by the other will evidently result in self-destruction of the entire life on earth. In this light, Human Animal Studies in Literature studies the representation, perception and treatment of non-human animals in works of fiction and non-fiction. This paper traces the origin of maltreatment of the animals that included killing of animals for the sake of entertainment. The paper investigates numerous Shikari narratives or the narratives of hunting expeditions recorded during the colonial times in the city of Bangalore. The paper shows how the perspective changed later because of the awareness that arose about the need to protect the Tigers in the post colonial era. R. K. Narayan's novel A Tiger for Malgudi is a fiction that originated in the post colonial times when the call for safeguarding the dying tigers was not loud enough to be heard. R. K. Narayan is said to have consulted the tiger expert Ullas Karanth while writing the novel A Tiger for Malgudi. The novel offers a representation of the non-human animal, the tiger, ascribing it human subjectivity. The first person narrative of a tiger in the novel marks the shift from the colonial perception of the Tiger as an animal to be subjugated to Tiger as a being with individual subjectivity.
Keywords: Human Animal Studies (Has); Colonialism; Anthropomorphism; Eco Criticism; Shikar Narratives